Catalytic cracking reaction method and catalytic cracking auxiliary agent
By modifying ZSM-5 molecular sieve with small-molecular phosphorus compounds such as hypophosphoric acid or ammonium hypophosphate, the activation and coordination between phosphorus and the skeleton aluminum is promoted, and the problem of phosphorus self-polymerization in the prior art is solved, and the catalytic cracking reaction is improved Hydrothermal stability and low-carbon olefin selectivity achieve higher ethylene and propylene yields.
Patent Information
- Application Number
- CN202310787365.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, phosphoric acid or ammonium phosphate salts are dehydrated and self-condensed during the roasting process, resulting in enrichment of the surface of ZSM-5 molecular sieve, blocking the pores, reducing the pore volume and specific surface area, and thus reducing the activation efficiency of phosphorus aluminum, which is unable to be effective. Improve hydrothermal stability and low-carbon olefin selectivity.
Modified ZSM-5 molecular sieve with inorganic phosphorus compounds with valence states of +1 valence and small molecules to promote the activation and coordination of phosphorus and skeleton aluminum, improve the hydrothermal stability of molecular sieve and low-carbon olefins Selectively, the hydrothermal aging treatment at 800°C and 100% water vapor conditions ensures the migration and activation of phosphorus species in the pores.
The hydrothermal stability and low-carbon olefin selectivity of phosphorus-modified ZSM-5 molecular sieve are significantly improved, and the activity of catalytic cracking reaction and the yield of ethylene and propylene are improved.
Smart Images

Figure CN119219458A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalytic cracking reaction method and an auxiliary agent used in the method, and more specifically to a catalytic cracking reaction method and a catalytic cracking auxiliary agent containing phosphorus-modified ZSM-5 molecular sieve. Background Art
[0002] The cracking reaction of hydrocarbons at high temperature converts long-chain hydrocarbons into high-value-added low-carbon olefins such as ethylene and propylene. ZSM-5 molecular sieve is a medium-pore molecular sieve with high silicon three-dimensional straight channels and MFI structure developed by Mobil Oil Company of the United States (USP3702886). Its unique pore structure gives it good shape-selective catalytic and isomerization performance. ZSM-5 molecular sieve also has the characteristics of high thermal and hydrothermal stability, high specific surface area, wide range of silicon-aluminum ratio, unique surface acidity and low carbon deposition. ZSM-5 molecular sieve is widely used as a catalyst and catalyst carrier, and has been successfully used in production processes such as alkylation, isomerization, disproportionation, catalytic cracking, methanol to gasoline, and methanol to olefins.
[0003] Since 1983, ZSM-5 molecular sieve has been used in catalytic cracking process as a catalytic cracking octane number aid, aiming to improve the octane number of catalytic cracking gasoline and the selectivity of light olefins. In the technology first reported in US3758403, ZSM-5 was used as an active component to increase the production of propylene, and was prepared into FCC catalyst together with REY. US5997728 discloses a technology of using ZSM-5 molecular sieve as an aid to increase the production of propylene, and the molecular sieve is not modified in any way. The propylene yield in the above two technologies is not high. Although HZSM-5 molecular sieve has good shape selectivity and isomerization performance, its disadvantage is poor hydrothermal stability and easy deactivation under harsh high-temperature hydrothermal conditions, which reduces the catalytic performance.
[0004] Mobil Corporation has found that phosphorus can improve the hydrothermal stability of ZSM-5 molecular sieves. At the same time, phosphorus modification of ZSM-5 molecular sieves can selectively convert primary cracking products (such as gasoline olefins) into C3 and C4 olefins, thereby increasing the yield of low-carbon olefins. ZSM-5 molecular sieves can be modified by introducing an appropriate amount of inorganic phosphorus compounds after synthesis to stabilize the framework aluminum under harsh hydrothermal conditions.
[0005] CN1211469A discloses a five-membered ring molecular sieve composition for producing more propylene and ethylene, which is composed of 85-95% by weight of a five-membered ring molecular sieve, 2-10% by weight of phosphorus calculated as oxide, 0.3-5% by weight of alkaline earth metal calculated as oxide, and 0.3-5% by weight of transition metal element calculated as oxide. The composition is used for catalytic thermal cracking reaction to obtain a higher ethylene yield.
[0006] US5171921 discloses a phosphorus-modified ZSM-5 molecular sieve having a silicon-aluminum ratio of 20-60. When HZSM-5 molecular sieve is impregnated with a phosphorus-containing compound and treated with 500-700°C steam, it has a higher activity than HZSM-5 without phosphorus treatment when used for the reaction of converting C3-C20 hydrocarbons into C2-C5 olefins.
[0007] CN102166533A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises adding the molecular sieve to a phosphorus-containing aqueous solution, reacting for a period of time at a certain pH value, temperature and pressure, and then filtering, drying and calcining to obtain the phosphorus-modified molecular sieve. Thereafter, the phosphorus-modified molecular sieve is added to an aqueous solution containing rare earth ions, reacting for a period of time at a certain temperature and pressure, and then filtering, washing, drying and calcining to obtain a composite modified molecular sieve. The composite modified molecular sieve is used to prepare a model catalyst having higher hydrothermal stability and micro-activity than the unmodified molecular sieve model catalyst and the molecular sieve model catalyst modified by other methods.
[0008] CN106994364A discloses a method for preparing a phosphorus-modified ZSM-5 molecular sieve, which comprises first mixing one or more phosphorus-containing compounds selected from phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate with a ZSM-5 molecular sieve having a high alkali metal ion content to obtain a mixture having a phosphorus loading of at least 0.1 wt% in terms of P2O5, drying and roasting the mixture, and then performing an ammonium crosslinking step and a water washing step to reduce the alkali metal ion content therein to below 0.10 wt%, and then undergoing drying and hydrothermal aging steps at 400-1000°C and 100% water vapor. The phosphorus-containing ZSM-5 molecular sieve obtained by the preparation method has a high total acid content, excellent cracking conversion rate and propylene selectivity, and also has a high liquefied gas yield.
[0009] Although the use of organic / inorganic phosphorus-containing compounds to modify ZSM-5 molecular sieves can inhibit skeleton dealumination and thus improve hydrothermal stability, and the introduction of phosphorus species also has the effect of regulating the properties of the acid center of the ZSM-5 molecular sieve, thereby improving the cracking conversion rate of long-chain alkanes and the selectivity of light olefins, in the roasting process of the prior art, phosphoric acid or ammonium phosphate will self-polymerize due to dehydration to form large molecular phosphorus species such as polyphosphoric acid, which are easily enriched on the outer surface of the molecular sieve, blocking the pores, reducing the pore volume and specific surface area, resulting in a low phosphorus-aluminum activation efficiency, and the ideal effect of improving hydrothermal stability cannot be achieved after phosphorus modification. Summary of the invention
[0010] Based on a large number of experiments, the inventors found that treating ZSM-5 molecular sieves with inorganic phosphorus compounds with a valence state of +1 and smaller molecules, such as hypophosphorous acid and ammonium hypophosphite, as phosphorus sources can promote the activation coordination effect between phosphorus and framework aluminum. The phosphorus-modified ZSM-5 molecular sieve obtained by the treatment has physicochemical characteristics different from those of conventional phosphorus-containing ZSM-5 molecular sieves. The phosphorus-aluminum stabilization efficiency of the molecular sieve is improved, and it has good hydrothermal stability, especially when used in catalytic cracking. It can be used as an auxiliary agent in combination with a catalytic cracking catalyst to achieve the technical effect of improving both cracking activity and low-carbon olefin selectivity.
[0011] Therefore, one of the objects of the present invention is to provide a catalytic cracking reaction method with the participation of a catalytic cracking aid having as an active component a phosphorus-modified ZSM-5 molecular sieve with physicochemical characteristics different from those of conventional phosphorus-containing ZSM-5 molecular sieves and improved phosphorus-aluminum stabilization efficiency of the molecular sieve; a second object is to provide a catalytic cracking aid used in the reaction method.
[0012] In order to achieve one of the above-mentioned purposes, the first aspect of the present invention provides a catalytic cracking reaction method, which is to contact hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, characterized in that the auxiliary agent is based on the dry weight of the auxiliary agent and is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70% of inorganic binder on a dry basis and 2-60% of clay on a dry basis, wherein the phosphorus-modified ZSM-5 molecular sieve, after hydrothermal aging at 800°C and 100% water vapor for 17 hours, has a binding energy of phosphorus element in phosphorus species on the surface of the molecular sieve of 134.6-134.7 eV, 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
[0013] In order to achieve the second purpose of the above, the second aspect of the present invention provides a catalytic cracking aid, characterized in that, based on the dry weight of the catalytic aid, it is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70% of inorganic binder on a dry basis and 2-60% of clay on a dry basis, wherein the phosphorus-modified ZSM-5 molecular sieve, after hydrothermal aging at 800° C. and 100% water vapor for 17 hours, has a binding energy of phosphorus element in phosphorus species on the surface of the molecular sieve of 134.6 to 134.7 eV, 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
[0014] The catalytic cracking reaction method provided by the present invention is carried out in the presence of a catalytic cracking aid containing a phosphorus-modified ZSM-5 molecular sieve with special physicochemical parameters; the phosphorus-modified ZSM-5 molecular sieve with special physicochemical parameters is obtained by selecting a +1-valent phosphorus source with relatively small molecules for modification; the +1-valent phosphorus source accelerates the migration process of phosphorus species into the pores of the ZSM-5 molecular sieve and accelerates the activation efficiency of phosphorus-aluminum species; the phosphorus species has an obvious coordination effect with framework aluminum, so that the framework aluminum is fully protected and has a higher crystal retention degree (95% to 110%) after hydrothermal aging at 800°C and 100% water vapor for 17 hours; the phosphorus-modified ZSM-5 molecular sieve is used as an active component cracking aid in a catalytic cracking reaction to improve the selectivity of ethylene and propylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The phosphorus-modified ZSM-5 molecular sieve samples JCB-1 and DPB-1 27 Al MAS-NMR spectrum.
[0016] Figure 2 XPS (P2p Scan) spectra of phosphorus-modified ZSM-5 molecular sieve samples JCB-1 and DPB-1.
[0017] Figure 3 The phosphorus-modified ZSM-5 molecular sieve samples JCB-2 and DPB-3 27 Al MAS-NMR spectrum.
[0018] Figure 4 This is the XPS (P2p Scan) spectrum of the phosphorus-modified ZSM-5 molecular sieve sample JCB-2.
[0019] Figure 5 The phosphorus-modified ZSM-5 molecular sieve samples JNB-3 and DPB-5 27 Al MAS-NMR spectrum.
[0020] Figure 6 This is the XPS (P2p Scan) spectrum of the phosphorus-modified ZSM-5 molecular sieve sample JNB-3. DETAILED DESCRIPTION
[0021] A catalytic cracking reaction method provided in the first aspect of the present invention is to contact hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, characterized in that the auxiliary agent is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve on a dry basis, 1-70% of inorganic binder on a dry basis and 2-60% of clay on a dry basis based on the dry basis weight of the auxiliary agent, wherein the phosphorus-modified ZSM-5 molecular sieve has an electron binding energy of 134.2-134.3 eV in the surface phosphorus species after drying at 120° C. in the atmosphere of air during the preparation process, and after hydrothermal aging at 800° C. and 100% water vapor for 17 hours, the binding energy of the phosphorus element in the phosphorus species on the surface of the molecular sieve is 134.6-134.7 eV. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
[0022] The binding energy of phosphorus characterized by XPS represents its chemical environment and valence state, and can explain the degree of polycondensation and valence state transformation of phosphorus species during drying and hydrothermal aging. In the present invention, the phosphorus-modified ZSM-5 molecular sieve is modified with a phosphorus-containing compound with a phosphorus valence state of +1. During the preparation process, the electron binding energy of the phosphorus element in the surface phosphorus species after drying at 120°C in the atmosphere of air is 134.2-134.3eV, and after hydrothermal aging for 17h at 800°C and 100% water vapor, the binding energy of phosphorus is 134.6-134.7eV. The molecular sieve modified with phosphoric acid in the prior art has almost no valence state transformation, so the binding energy of drying and aging is 134.8-134.9eV.
[0023] In the present invention, the phosphorus-modified ZSM-5 molecular sieve is subjected to hydrothermal aging at 800°C and 100% steam for 17 hours. 27 Al MAS-NMR test characterization, 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3ppm is 10 to 25ppm; preferably, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3ppm is 15 to 25ppm. The resonance signal with a chemical shift of 39±3ppm represents a framework aluminum species that is stabilized after coordination with a phosphorus species, that is, a distorted four-coordinate framework aluminum. The larger the full width at half maximum of 39±3ppm, the more the number and types of framework aluminum stabilized by phosphorus, and the specific combination form of phosphorus-aluminum species may also be different. The prior art ZSM-5 molecular sieve modified with a phosphorus-containing precursor such as diammonium hydrogen phosphate or phosphoric acid with a phosphorus valence of +5 has a full width at half maximum of 5 to 10ppm.
[0024] In the present invention, the phosphorus-modified ZSM-5 molecular sieve has a higher crystal retention (95% to 110%) after hydrothermal aging at 800°C and 100% water vapor for 17 hours, which also shows that the phosphorus species has a significant coordination effect with the framework aluminum, so that the framework aluminum is fully protected and the molecular sieve has excellent hydrothermal stability.
[0025] In the present invention, the phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
[0026] In the present invention, preferably, the phosphorus-modified ZSM-5 molecular sieve is obtained by contacting the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +1 at room temperature, such as 20-25°C, and then drying and calcining it; or the mixture obtained by mixing and grinding the HZSM-5 molecular sieve with a solid phosphorus-containing compound with a phosphorus valence state of +1 is heated and melted, cooled to room temperature, such as 20-25°C, and then calcined. The impregnation is carried out at a water-to-sieve weight ratio of 0.5 to 2 at room temperature for 0.5 to 10 hours; the drying is carried out in an atmosphere of air at 100 to 120°C for 2 to 24 hours, and it can be seen from the XPS (P2p Scan) spectrum that the binding energy of the phosphorus element in the surface phosphorus species is 134.2 to 134.3 eV; the calcination is carried out in an atmosphere of air at 200 to 800°C for 0.5 to 12 hours. The heating and melting treatment has a temperature higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates, and the treatment time is 2 to 72 hours.
[0027] In the present invention, the phosphorus-containing compound with a phosphorus valence state of +1 is selected from one or more of hypophosphorous acid, ammonium hypophosphite, and hypophosphite; or, the phosphorus-containing compound aqueous solution with a phosphorus valence state of +1 is obtained by adjusting the pH value of an aqueous solution of hypophosphorous acid to 5-9 with ammonia water. The molar ratio of the HZSM-5 molecular sieve to the phosphorus-containing compound with a phosphorus valence state of +1 is (0.1-2.5):1, preferably (0.5-1.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum and the phosphorus-containing compound is calculated as phosphorus. The HZSM-5 molecular sieve is obtained by reducing the sodium content of ZSM-5 molecular sieve to Na2O<0.1wt% through ammonium exchange, and the silicon-aluminum ratio (molar ratio of silicon oxide to aluminum oxide, the same below) ranges ≥10, usually 10-200.
[0028] Regarding the phosphorus-modified ZSM-5 molecular sieve involved in the above-mentioned application, this application also introduces the contents of the Chinese invention application with application number 202210884623.4 and application date July 26, 2022 for reference.
[0029] In the present invention, in the mixture of the cracking catalyst and an auxiliary agent, the content of the auxiliary agent is preferably 0.1 to 30% by weight.
[0030] The cracking catalyst may be a catalytic cracking catalyst commonly used in the art, and its composition includes a common molecular sieve active component of the cracking catalyst, an inorganic binder, clay, etc. The molecular sieve active component of the cracking catalyst includes a Y-type molecular sieve. The Y-type molecular sieve is selected from at least one of PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.
[0031] In the present invention, the hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products. The hydrocarbon oil may contain heavy metal impurities such as nickel and vanadium and sulfur and nitrogen impurities, such as the sulfur content in the hydrocarbon oil may be as high as 3.0% by weight, the nitrogen content may be as high as 2.0% by weight, and the content of metal impurities such as vanadium and nickel may be as high as 3000ppm.
[0032] In the present invention, the catalytic cracking reaction conditions may be conventional in the art, preferably including: a reaction temperature of 500 to 800°C, such as 550 to 680°C.
[0033] The second aspect of the present invention provides a catalytic cracking aid, characterized in that, based on the dry weight of the catalytic aid, it is composed of 20-80 weight percent of phosphorus-modified ZSM-5 molecular sieve, 1-70 weight percent of inorganic binder, and 2-60 weight percent of clay, wherein the phosphorus-modified ZSM-5 molecular sieve has a binding energy of phosphorus element in phosphorus species on the surface of the molecular sieve of 134.6-134.7 eV after hydrothermal aging at 800° C. and 100% water vapor for 17 hours. 27 In the AlMAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
[0034] The phosphorus-modified ZSM-5 molecular sieve in the additive was subjected to hydrothermal aging at 800°C and 100% steam for 17 hours and its 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak having a chemical shift of 39±3 ppm is preferably 15 to 25 ppm.
[0035] The phosphorus-modified ZSM-5 molecular sieve in the auxiliary agent has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
[0036] The phosphorus-modified ZSM-5 molecular sieve in the auxiliary agent is preferably obtained by impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound with a phosphorus valence state of +1 at room temperature, such as 20-25°C, followed by drying and roasting; or by heating and melting the mixture obtained by mixing and grinding the HZSM-5 molecular sieve with a solid phosphorus-containing compound with a phosphorus valence state of +1, cooling it to room temperature, such as 20-25°C, and then roasting it. Wherein, the water-to-sieve weight ratio of the impregnation is 0.5-2, and it is carried out at room temperature for 0.5-10 hours; the drying is carried out in an atmosphere of air at 100-120°C for 2-24 hours; the roasting is carried out in an atmosphere of air at 200-800°C for 0.5-12 hours. The heating and melting treatment is carried out at a temperature higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates, and the treatment time is 2-72 hours. The phosphorus-containing compound with a phosphorus valence state of +1 is selected from one or more of hypophosphorous acid, ammonium hypophosphite, and hypophosphite; or, the aqueous solution of the phosphorus-containing compound with a phosphorus valence state of +1 is an aqueous solution of hypophosphorous acid adjusted to a pH value of 5-9 with ammonia water.
[0037] The catalytic cracking aid provided by the present invention preferably comprises 20-75 wt % of the phosphorus-modified ZSM-5 molecular sieve based on dry basis, and further comprises 25-70 wt % of the phosphorus-modified molecular sieve based on dry basis.
[0038] The inorganic binder in the auxiliary agent may include a phosphorus-aluminum inorganic binder and / or other inorganic binders. Preferably, the inorganic binder may include 2-45 wt % of the phosphorus-aluminum inorganic binder on a dry basis and 5-30 wt % of the other inorganic binders on a dry basis.
[0039] Based on the dry weight of the phosphorus-aluminum inorganic binder, the phosphorus-aluminum inorganic binder includes 15-40 weight% of aluminum component calculated as Al2O3, 45-80 weight% of phosphorus component calculated as P2O5, and its P / Al weight ratio is 1.0-6.0, the pH value is 1-3.5, and the solid content is 15-60 weight%; for example, it includes 15-40 weight% of aluminum component calculated as Al2O3, 45-80 weight% of phosphorus component calculated as P2O5; preferably it contains 15-35 weight% of aluminum component calculated as Al2O3, 50-75 weight% of phosphorus component calculated as P2O5, and its P / Al weight ratio is preferably 1.2-6.0, more preferably 2.0-5.0, and the pH value is preferably 1.5-3.0. Preferably, the phosphorus-aluminum inorganic binder comprises 20-40 wt% aluminum component in terms of Al2O3 and 60-80 wt% phosphorus component in terms of P2O5, based on the dry weight. The phosphorus-aluminum inorganic binder can be prepared by the following steps: alumina source, clay (e.g., rectorite, kaolin) and water are slurried and dispersed into a slurry with a solid content of 5-50 wt%; wherein the alumina source is aluminum hydroxide and / or aluminum oxide (e.g., pseudo-boehmite, SB powder, γ-alumina) that can be peptized by acid, relative to 15-50 weight parts of the alumina source in terms of Al2O3; concentrated phosphoric acid is added to the slurry at a weight ratio of P / Al=1-6 under stirring, and the resulting mixed slurry is reacted at 50-99°C for 15-90 minutes; wherein P in P / Al is the weight of phosphorus in phosphoric acid in terms of elemental substance, and Al is the weight of aluminum in the alumina source in terms of elemental substance.
[0040] The other inorganic binder is selected from at least one of pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.
[0041] In the auxiliary agent provided by the present invention, the clay is well known to those skilled in the art, and the clay can be at least one selected from kaolin, metakaolin, diatomaceous earth, sepiolite, attapulgite, montmorillonite and rectorite, preferably kaolin, metakaolin and rectorite. Based on the dry weight of the auxiliary agent, the clay is contained in an amount of 2-60% by weight, preferably 5-55% by weight, and more preferably 15-40% by weight.
[0042] In a specific preparation embodiment of the auxiliary agent of the present invention, an inorganic binder (such as pseudo-boehmite, aluminum sol, silica sol, silica-alumina gel or a mixture of two or more thereof) can be mixed with clay (such as kaolin) and water (such as deionized water and / or deionized water) to form a slurry with a solid content of 10 to 50% by weight, and stirred evenly. The slurry pH is adjusted to 1 to 4 with an inorganic acid such as hydrochloric acid, nitric acid, phosphoric acid or sulfuric acid, and the pH value is maintained. After aging at 20 to 80° C. for 0 to 2 hours, such as 0.3 to 2 hours, aluminum sol and / or silica sol are added, stirred for 0.5 to 1.5 hours to form a colloid, and then a phosphorus-modified ZSM-5 molecular sieve is added to form a catalyst slurry. The solid content of the catalyst slurry is, for example, 20 to 45 weight%, and the stirring is continued and then spray-dried to form microspheres. The microspheres are then calcined, for example, at 350-650°C or 400-600°C, preferably 450-550°C, for 0.5-6 hours or 0.5-2 hours, and then washed with ammonium sulfate (wherein the washing temperature can be 40-70°C, ammonium sulfate: microspheres: water = 0.2-0.8:1:5-15 weight ratio) until the sodium oxide content is less than 0.25% by weight, washed with water and filtered, and then dried.
[0043] In another specific preparation embodiment of the auxiliary agent of the present invention, the phosphorus-modified ZSM-5 molecular sieve, the phosphorus-aluminum inorganic binder and other inorganic binders can be mixed, clay is added, slurried, and spray-dried.
[0044] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0045] X-ray diffraction (XRD) spectra were measured on a Rigaku TTR-3 powder X-ray diffractometer. Instrument parameters: copper target (tube voltage 40 kV, tube current 250 mA), scintillation counter, step width 0.02°, scanning rate 0.4 (°) / min. The ZSM-5 molecular sieve synthesized by the method of Example 1 in CN1056818C was used as a standard sample, and its crystallinity was set to 100%. The relative crystallinity is expressed as a percentage of the sum of the peak areas of the five characteristic diffraction peaks at 2θ between 22.5 and 25.0° of the X-ray diffraction spectra of the obtained product and the standard sample.
[0046] 27 Al MAS-NMR spectrum analysis was performed on a Bruker AVANCE III 600WB spectrometer. Instrument parameters: rotor diameter 4 mm, resonance spectrum 156.4 MHz, pulse width 0.4 μs (corresponding to 15° bevel angle), magic angle rotation speed 12 kHz, delay time 1 s. 27The characteristics of the Al MAS-NMR spectrum are that the characteristic peak 1 at 54±3 ppm is attributed to the tetracoordinated framework aluminum, and the characteristic peak 2 at 39±3 ppm is attributed to the phosphorus-stabilized framework aluminum (distorted tetracoordinated framework aluminum). The area of each peak is calculated by the integration method after peak fitting of the characteristic peaks.
[0047] X-ray photoelectron spectroscopy (XPS) was used to analyze the molecular sieve surface and examine the migration of phosphorus compounds using the ESCALAB 250 X-ray photoelectron spectrometer from Thermo Fisher-VG. Instrument parameters: The excitation source was monochromatic AlKα X-ray with a power of 150 W, and the charge shift was corrected using the C1s peak (284.8 eV) from contaminated carbon.
[0048] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.
[0049] The properties of some of the raw materials used in the examples are as follows:
[0050] Pseudo-boehmite is an industrial product produced by Shandong Aluminum Company, with a solid content of 60% by weight.
[0051] Alumina sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with an Al2O3 content of 21.5% by weight.
[0052] Silica sol is an industrial product produced by Sinopec Catalyst Qilu Branch, with a SiO2 content of 28.9% by weight and a Na2O content of 8.9%.
[0053] The kaolin is kaolin specially used for catalytic cracking catalyst produced by Suzhou Kaolin Company, with a solid content of 78% by weight.
[0054] The rectorite was produced by Hubei Zhongxiang Mingliu Rectorite Development Co., Ltd., with a quartz sand content of <3.5% by weight, an Al2O3 content of 39.0% by weight, a Na2O content of 0.03% by weight, and a solid content of 77% by weight.
[0055] SB aluminum hydroxide powder, produced by Condex, Germany, has an Al2O3 content of 75% by weight.
[0056] HRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a rare earth content of 10% by weight.
[0057] PSRY molecular sieve is an industrial product produced by Sinopec Catalyst Changling Branch, with a Na2O content of <1.5% by weight, a P2O5 content of 0.8-1.2% by weight, a unit cell constant of <2.456nm, and a crystallinity of ≥64%.
[0058] Unless otherwise specified, the instruments and reagents used in the embodiments of the present invention are commonly used by those skilled in the art.
[0059] Examples 1-13 illustrate the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention and its preparation.
[0060] Example 1
[0061] Example 1 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 1.0.
[0062] Take 6.9g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-modified ZSM-5 molecular sieve sample is recorded as JCB-1.
[0063] Example 2
[0064] Example 2 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention. The phosphorus-to-aluminum ratio is 1.0.
[0065] 8.7 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-modified ZSM-5 molecular sieve sample was recorded as JNB-1.
[0066] Example 3
[0067] Example 3 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention. The phosphorus-to-aluminum ratio is 1.0.
[0068] Take 6.9g of solid hypophosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C and a time of 10h. After the melting process, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RCB-1.
[0069] Example 4
[0070] Example 4 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention. The phosphorus-to-aluminum ratio is 1.0.
[0071] 8.7 g of solid ammonium hypophosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature; the above sample was calcined at 550°C for 2 h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-1.
[0072] Comparative Example 1
[0073] Take 13.9g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-1.
[0074] Comparative Example 2
[0075] Take 12.1g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-2.
[0076] The XRD relative crystallinity and crystal retention of samples JCB-1, JNB-1, RCB-1, RNB-1, and comparison samples DPB-1 and DPB-2 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 1.
[0077] Sample JCB-1 and comparison sample DPB-1 27 Al MAS-NMR spectrum is shown in Figure 1 . Figure 1 The characteristic peak with a chemical shift of 39 ppm is attributed to the distorted four-coordinated framework aluminum formed by the combination of phosphorus and aluminum, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JCB-1 Figure 1 The features are the same.
[0078] The full width at half maximum of the characteristic peaks at the chemical shift of samples JCB-1, JNB-1, RCB-1, RNB-1, and comparative samples DPB-1 and DPB-2 at 39 ppm are shown in Table 2.
[0079] The XPS (P2p Scan) spectra of sample JCB-1 and comparative sample DPB-1 are shown in Figure 2 In the figure, the peaks 134.2eV and 134.6eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-1 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-1 after hydrothermal aging at 800°C and 100% water vapor for 17 hours, respectively. 134.8eV and 134.9eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of the comparative sample DPB-1 after corresponding drying and hydrothermal aging, respectively. The XPS (P2p Scan) spectral characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples JNB-1, RCB-1, and RNB-1 after hydrothermal aging at 800°C and 100% water vapor for 17 hours are similar to those of sample JCB-1. Figure 2 The features are the same.
[0080] Table 1
[0081]
[0082] Table 2
[0083] sample 39ppm characteristic peak half-peak full width / ppm JCB-1 17 JNB-1 19 RCB-1 16 RNB-1 18 DPB-1 7 DPB-2 9
[0084] Example 5
[0085] Example 5 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 0.5.
[0086] Take 3.45g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JCB-2.
[0087] Example 6
[0088] Example 6 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 0.5.
[0089] Take 4.4g of ammonium hypophosphite and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JNB-2.
[0090] Example 7
[0091] Example 7 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 0.5.
[0092] Take 3.45g of solid hypophosphorous acid and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C and a time of 10h. After the end, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RCB-2.
[0093] Example 8
[0094] Example 8 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 0.5.
[0095] Take 4.4g of solid ammonium hypophosphite and add it to 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30). After grinding and mixing for 0.5h, transfer it to a Teflon-lined stainless steel high-pressure reactor for a melting process with a heating temperature of 40°C and a time of 10h. After the end, wait for the sample to naturally cool to room temperature and then take it out; the above sample is calcined at 550°C for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-2.
[0096] Comparative Example 3
[0097] Take 6.95g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-3.
[0098] Comparative Example 4
[0099] Take 6.05g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-4.
[0100] The XRD relative crystallinity and crystal retention of samples JCB-2, JNB-2, RCB-2, RNB-2, and comparison samples DPB-3 and DPB-4 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 3.
[0101] Sample JCB-2 and comparative sample DPB-3 27 Al MAS-NMR spectrum is shown in Figure 3 In the figure, the characteristic peak with chemical shift at 39 ppm is attributed to the distorted four-coordinated framework aluminum formed after phosphorus and aluminum combine, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JCB-2 Figure 3 The features are the same.
[0102] The characteristic peak with chemical shift at 39 ppm for samples JCB-2, JNB-2, RCB-2, RNB-2, and comparative samples DPB-3 and DPB-4 is shown in Table 4.
[0103] The XPS (P2p Scan) spectrum of sample JCB-2 is shown in Figure 4 In the figure, the peaks 134.3eV and 134.7eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-2 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JCB-2 after hydrothermal aging at 800°C and 100% water vapor for 17h. The XPS (P2p Scan) spectrum characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples JNB-2, RCB-2, and RNB-2 after hydrothermal aging at 800°C and 100% water vapor for 17h are similar to those of sample JCB-2. Figure 4 The features are the same.
[0104] Table 3
[0105]
[0106] Table 4
[0107] sample 39ppm characteristic peak half-peak full width / ppm JCB-2 17 JNB-2 19 RCB-2 18 RNB-2 19 DPB-3 8 DPB-4 8
[0108] Example 9
[0109] Example 9 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 1.5.
[0110] 13.02 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-containing ZSM-5 molecular sieve sample was recorded as JNB-3.
[0111] Example 10
[0112] Example 10 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 1.5.
[0113] 13.02 g of ammonium hypophosphite was added to 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), which was ground and mixed for 0.5 h and then transferred to a Teflon-lined stainless steel high-pressure reactor for a melting process at a heating temperature of 40°C for 10 h. After the melting process, the sample was taken out after naturally cooling to room temperature. The above sample was calcined at 550°C for 2 h to obtain a phosphorus-containing ZSM-5 molecular sieve sample, recorded as RNB-3.
[0114] Embodiment 11
[0115] Example 11 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a phosphorus-to-aluminum ratio of 1.5.
[0116] Take 10.35g of hypophosphorous acid and dissolve it in 145g of deionized water at 25°C, add ammonia water to adjust the pH value of the solution to 5-9, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JCB-4.
[0117] Comparative Example 5
[0118] Take 20.85g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-5.
[0119] Comparative Example 6
[0120] Take 18.15g of phosphoric acid solution (mass fraction 85wt%) and dissolve it in 145g of deionized water at 25℃, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=30), and modify it by impregnation method. After impregnation at 25℃ for 0.5h, move it to an oven and dry it at 120℃ for 12h, and calcine it at 550℃ in an air atmosphere in a muffle furnace for 2h to obtain a phosphorus-containing ZSM-5 molecular sieve comparison sample, recorded as DPB-6.
[0121] The XRD relative crystallinity and crystal retention of samples JNB-3, RNB-3, JCB-4, and comparison samples DPB-5 and DPB-6 before and after hydrothermal aging at 800°C, 100% water vapor, and 17h are shown in Table 5.
[0122] Sample JNB-3 and comparative sample DPB-5 27 Al MAS-NMR spectrum is shown in Figure 5 In the figure, the characteristic peak with chemical shift at 39 ppm is attributed to the distorted four-coordinated framework aluminum formed after phosphorus and aluminum combine, that is, the framework aluminum stabilized by phosphorus species. 27 Al MAS-NMR spectrum characteristics and sample JNB-3 Figure 5 The features are the same.
[0123] The full width at half maximum of the characteristic peaks with chemical shifts at 39 ppm for samples JNB-3, RNB-3, JCB-4, and comparative samples DPB-5 and DPB-6 are shown in Table 6.
[0124] The XPS (P2p Scan) spectrum of sample JNB-3 is shown in Figure 6In the figure, the peaks 134.3eV and 134.6eV represent the electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-3 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-3 after hydrothermal aging at 800°C and 100% water vapor for 17h. The XPS (P2p Scan) spectrum characteristics of the electron binding energy of the phosphorus element in the surface phosphorus species of samples RNB-3 and JCB-4 after hydrothermal aging at 800°C and 100% water vapor for 17h are similar to those of sample JNB-3. Figure 6 The features are the same.
[0125] Table 5
[0126]
[0127] Table 6
[0128] sample 39ppm characteristic peak half-peak full width / ppm JNB-3 19 RNB-3 20 JCB-4 19 DPB-5 7 DPB-6 9
[0129] Example 12
[0130] Example 12 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalytic cracking aid of the present invention, with a silicon-aluminum ratio of 100 and a phosphorus-aluminum ratio of 1.0.
[0131] 1.36 g of ammonium hypophosphite was dissolved in 145 g of deionized water at 25 ° C, stirred for 0.5 h to obtain a phosphorus-containing aqueous solution, 100 g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=100) was added, and modified by impregnation method. After impregnation at 25 ° C for 0.5 h, it was moved to an oven for drying at 120 ° C for 12 h, and calcined at 550 ° C in an air atmosphere in a muffle furnace for 2 h. The obtained phosphorus-containing ZSM-5 molecular sieve sample was recorded as JNB-5.
[0132] Comparative Example 7
[0133] Take 2.16g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=100), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-7.
[0134] Embodiment 13
[0135] Example 12 illustrates the phosphorus-modified ZSM-5 molecular sieve used in the catalyst of the present invention, with a silicon-to-aluminum ratio of 150 and a phosphorus-to-aluminum ratio of 1.0.
[0136] Take 0.91g of ammonium hypophosphite and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=150), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve sample is recorded as JNB-6.
[0137] Comparative Example 8
[0138] Take 1.45g of diammonium hydrogen phosphate and dissolve it in 145g of deionized water at 25°C, stir for 0.5h to obtain a phosphorus-containing aqueous solution, add 100g of HZSM-5 molecular sieve (nSiO2 / nAl2O3=150), and modify it by impregnation method. After impregnation at 25°C for 0.5h, move it to an oven and dry it at 120°C for 12h, and calcine it at 550°C in an air atmosphere in a muffle furnace for 2h. The obtained phosphorus-containing ZSM-5 molecular sieve comparison sample is recorded as DPB-8.
[0139] The XRD relative crystallinity and crystal retention of sample JNB-5, comparative sample DPB-7, JNB-6 and comparative sample DPB-8 before and after hydrothermal aging at 800°C, 100% water vapor and 17h are shown in Table 7, and the half-maximum full width data of the characteristic peak at the chemical shift of 39ppm in the 27Al MAS-NMR spectrum are shown in Table 8.
[0140] The electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-5 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species after hydrothermal aging at 800°C and 100% water vapor for 17 hours are 134.2eV and 134.7eV, respectively.
[0141] The electron binding energies of the phosphorus element in the surface phosphorus species of the comparative sample DPB-7 after drying and hydrothermal aging are 134.8 eV and 134.9 eV, respectively.
[0142] The electron binding energy of the phosphorus element in the surface phosphorus species of sample JNB-6 after drying at 120°C during the preparation process and the electron binding energy of the phosphorus element in the surface phosphorus species after hydrothermal aging at 800°C and 100% water vapor conditions for 17 hours are 134.3eV and 134.6eV, respectively.
[0143] The electron binding energies of the phosphorus element in the surface phosphorus species of the comparative sample DPB-8 after drying and hydrothermal aging are 134.8 eV and 135.0 eV, respectively.
[0144] Table 7
[0145]
[0146] Table 8
[0147] sample 39ppm characteristic peak half-peak full width / ppm JNB-5 19 DPB-7 18 JNB-6 9 DPB-8 8
[0148] Examples 14-26 illustrate the catalytic cracking aids of the present invention.
[0149] The phosphorus-aluminum inorganic binder used in the embodiment is prepared by the following process:
[0150] 1. NJ1: 1.91 kg of pseudo-boehmite (containing 1.19 kg of Al2O3), 0.56 kg of kaolin (0.5 kg on a dry basis) and 3.27 kg of decationized water were slurried for 30 minutes, and 5.37 kg of concentrated phosphoric acid (mass concentration 85%) was added to the slurry under stirring, with the phosphoric acid addition rate being 0.04 kg of phosphoric acid / min / kg of alumina source, and the temperature was raised to 70°C, and then reacted at this temperature for 45 minutes to obtain a phosphorus-aluminum inorganic binder. The material ratio is shown in Table 9, and the sample number is NJ1.
[0151] 2. NJ2: According to the preparation process of NJ1, the material ratio is shown in Table 9, and the sample number is NJ2.
[0152] Table 9
[0153]
[0154] Examples 14-17
[0155] Take the phosphorus-modified molecular sieve JCB-1, kaolin and pseudo-boehmite of Example 1, add decationized water and beat for 120 minutes to obtain a slurry with a solid content of 30 weight%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ1. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain an additive, No. Z1.
[0156] The molecular sieve JCB-1 was replaced by the phosphorus-modified molecular sieves JNB-1, RCB-1 and RNB-1 of Examples 2-4, respectively, and the additives were prepared by the same preparation process as above, numbered Z2, Z3 and Z4, respectively.
[0157] In the material proportions of Z1, Z2, Z3 and Z4, based on dry weight, phosphorus-modified molecular sieve accounts for 65%, kaolin accounts for 20%, phosphorus-aluminum binder NJ1 accounts for 10%, and pseudo-boehmite accounts for 5%.
[0158] Comparative Examples 9 and 10
[0159] The preparation process and material ratio are the same as those of Example 14, except that the phosphorus-modified molecular sieves DPB-1 and DPB-2 of Comparative Examples 1 and 2 are used to replace the molecular sieve JCB-1, to prepare comparative additives, numbered DZ1 and DZ2, respectively.
[0160] Examples 15-21
[0161] Take the phosphorus-modified molecular sieve JCB-2 and kaolin of Example 5, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, and then add the phosphorus-aluminum inorganic binder NJ2. After stirring for 30 minutes, the obtained slurry is spray-dried to obtain microspheres, and the microspheres are calcined at 500°C for 1 hour to obtain a catalyst, No. Z5.
[0162] The molecular sieve JCB-2 was replaced by the phosphorus-modified molecular sieves JNB-2, RCB-2 and RNB-2 of Examples 5-8, respectively, and the additives were prepared by the same preparation process as above, numbered Z6, Z7 and Z8, respectively.
[0163] In the material proportions of Z5, Z6, Z7 and Z8, based on dry weight, phosphorus-modified molecular sieve accounts for 55%, kaolin accounts for 30%, phosphorus-aluminum binder NJ2 accounts for 10%, and aluminum sol accounts for 5%.
[0164] Comparative Examples 11 and 12
[0165] The preparation process and material ratio are the same as those of Example 15, except that the phosphorus-modified molecular sieves DPB-3 and DPB-4 of Comparative Examples 3 and 4 are used to replace the molecular sieve JCB-2, respectively, to prepare comparative additives, numbered DZ3 and DZ4.
[0166] Examples 22-24
[0167] Take the phosphorus-modified molecular sieve JNB-3 and kaolin of Example 9, add decationized water and aluminum sol and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, then add the phosphorus-aluminum inorganic binder NJ1, stir for 30 minutes, spray dry the obtained slurry to obtain microspheres, calcine the microspheres at 500°C for 1 hour to obtain a catalyst, No. Z9.
[0168] The molecular sieve JNB-3 was replaced by the phosphorus-modified molecular sieves RNB-3 and JCB-4 of Examples 10 and 11, respectively, and the additives were prepared by the same preparation process as above, numbered Z10 and Z11, respectively.
[0169] In the material proportions of Z9, Z10 and Z11, calculated on a dry basis, the phosphorus-modified molecular sieve accounts for 60%, kaolin accounts for 20%, the phosphorus-aluminum binder NJ1 accounts for 10%, and the aluminum sol accounts for 10%.
[0170] Comparative Examples 13 and 14
[0171] The preparation process and material ratio are the same as those of Example 22, except that the phosphorus-modified molecular sieves DPB-5 and DPB-6 of Comparative Examples 5 and 6 are used to replace the molecular sieve JCB-3, respectively, to prepare comparative additives, numbered DZ5 and DZ6.
[0172] Embodiment 25, 26
[0173] Take the phosphorus-modified molecular sieve JNB-5 and kaolin of Example 12, add decationized water and beat for 120 minutes to obtain a slurry with a solid content of 30 wt%, add hydrochloric acid to adjust the pH value of the slurry to 3.0, and then continue to beat for 45 minutes, then add the phosphorus-aluminum inorganic binder NJ1, stir for 30 minutes, and then spray dry the obtained slurry to obtain microspheres. The microspheres are calcined at 500°C for 1 hour to obtain a catalyst, No. Z12.
[0174] The phosphorus-modified molecular sieve JNB-6 of Example 13 was used to replace the molecular sieve JNB-5, and the auxiliary agent was prepared in the same manner as the above preparation process, and the auxiliary agent was numbered Z13.
[0175] In the material proportions of Z12 and Z13, based on dry weight, phosphorus-modified molecular sieve accounts for 65%, kaolin accounts for 20%, and phosphorus-aluminum binder NJ1 accounts for 15%.
[0176] Comparative Example 15
[0177] The preparation process and material ratio are the same as those of Example 25, except that the phosphorus-modified molecular sieve DPB-7 of Comparative Example 7 is used instead of the molecular sieve JNB-5 to prepare a comparative auxiliary agent, numbered DZ7.
[0178] Comparative Example 16
[0179] The preparation process and material ratio are the same as those of Example 26, except that the phosphorus-modified molecular sieve DPB-8 of Comparative Example 8 is used instead of the molecular sieve JNB-6 to prepare a comparative auxiliary agent, numbered DZ8.
[0180] The following examples illustrate the catalytic cracking method provided by the present invention.
[0181] Examples 27-30
[0182] The additives Z1-Z4 were aged at 800°C in a 100% steam atmosphere for 17 hours.
[0183] The aged additive was mixed with an industrial FCC equilibrium catalyst (an industrial grade MMC equilibrium catalyst with a light oil micro-reaction activity of 63), and the additive accounted for 10% by weight of the mixture. The mixture was loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the additive on light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and an additive-to-oil ratio of 3.2.
[0184] The properties of crude oil I are shown in Table 10.
[0185] The reaction results are shown in Table 11.
[0186] Comparative Examples 17 and 18
[0187] Same as Example 27, except that comparative catalysts DC1 and DC2 were used to replace C1. The reaction results are shown in Table 11.
[0188] Table 10
[0189]
[0190]
[0191] Table 11
[0192]
[0193] Examples 31-34
[0194] The additives Z5-Z8 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged additives were mixed with an industrial FCC equilibrium catalyst (an industrial grade MMC equilibrium catalyst with a light oil micro-reaction activity of 63) and loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the additives for light hydrocarbons. The evaluation conditions were a reaction temperature of 650°C, a regeneration temperature of 620°C, and an agent-oil ratio of 3.2.
[0195] The reaction results are shown in Table 12.
[0196] Comparative Examples 19 and 20
[0197] Same as Example 31, except that comparative catalysts DZ3 and DZ4 were used to replace Z5. The reaction results are shown in Table 12.
[0198] Table 12
[0199]
[0200] Examples 35-37
[0201] Catalysts Z9-Z11 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were mixed with industrial FCC equilibrium catalysts (industrial grade MMC equilibrium catalysts, light oil micro-reaction activity of 63) and loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were reaction temperature of 650°C, regeneration temperature of 620°C, and catalyst-to-oil ratio of 3.2.
[0202] The reaction results are shown in Table 13.
[0203] Comparative Examples 21 and 22
[0204] Same as Example 35, except that comparative catalysts DZ5 and DZ6 were used to replace Z9. The reaction results are shown in Table 13.
[0205] Table 13
[0206]
[0207] Embodiment 38, 39
[0208] Catalysts Z12 and Z13 were aged for 17 hours at 800°C in a 100% steam atmosphere. The aged catalysts were mixed with industrial FCC equilibrium catalysts (industrial grade MMC equilibrium catalysts, light oil micro-reaction activity of 63) and loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the catalysts for light hydrocarbons. The evaluation conditions were reaction temperature of 650°C, regeneration temperature of 620°C, and catalyst-to-oil ratio of 3.2. The reaction results are shown in Table 14.
[0209] Comparative Examples 23 and 24
[0210] Same as Example 38, except that comparative catalysts DZ7 and DZ8 were used to replace Z12. The reaction results are shown in Table 14.
[0211] Table 14
[0212]
[0213] Examples 40-43
[0214] Catalysts Z1-Z4 were aged at 800°C in a 100% steam atmosphere for 17 hours. The aged catalysts were mixed with industrial FCC equilibrium catalysts (industrial grade MMC equilibrium catalysts, light oil micro-reaction activity of 63), and the aged catalysts were loaded into a fixed bed micro-reaction reactor to evaluate the catalytic cracking ability of the catalysts on n-tetradecane.
[0215] The evaluation conditions were reaction temperature 500°C, regeneration temperature 600°C, and catalyst-oil ratio 1.28. The reaction results are shown in Table 15.
[0216] Comparative Examples 25 and 26
[0217] Same as Example 40, except that comparative catalysts DZ1 and DZ2 were used to replace Z1. The reaction results are shown in Table 15.
[0218] Table 15
[0219]
[0220] It can be seen from Tables 11, 12, 13, 14 and 15 that the catalytic cracking aids prepared by modifying the ZSM-5 molecular sieve with phosphorus-containing compounds having a phosphorus valence state of +1 have higher hydrocarbon conversion rates, less coke, and higher ethylene and propylene yields than the catalytic cracking aids prepared by modifying the ZSM-5 molecular sieve with phosphorus-containing compounds having a phosphorus valence state of +5.
Claims
1. A catalytic cracking reaction method, comprising contacting a hydrocarbon oil with a mixture of a cracking catalyst and an auxiliary agent under catalytic cracking reaction conditions, characterized in that: The auxiliary agent is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve, 1-70% of inorganic binder and 2-60% of clay on a dry basis, based on the dry basis weight of the auxiliary agent. The phosphorus-modified ZSM-5 molecular sieve has a binding energy of phosphorus element in phosphorus species on the surface of the molecular sieve of 134.6-134.7 eV after hydrothermal aging at 800° C. and 100% water vapor for 17 hours. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
2. The catalytic cracking reaction method according to claim 1, wherein: The phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged at 800°C and 100% steam for 17 hours. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 15 to 25 ppm.
3. The catalytic cracking reaction method according to claim 1, characterized in that: The phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
4. The catalytic cracking reaction method according to claim 1, characterized in that: The phosphorus-modified ZSM-5 molecular sieve is obtained by impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound having a phosphorus valence state of +1 at room temperature, such as 20-25°C, followed by drying and calcining; or, the phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding the HZSM-5 molecular sieve and a solid phosphorus-containing compound having a phosphorus valence state of +1, heating and melting the mixture, cooling the mixture to room temperature, such as 20-25°C, and then calcining the mixture.
5. The catalytic cracking reaction method according to claim 1, wherein: In the mixture of the cracking catalyst and an auxiliary agent, the content of the auxiliary agent is 0.1 to 30 weight %.
6. The catalytic cracking reaction method according to claim 1 or 5, wherein: The active component of the cracking catalyst includes Y-type molecular sieve.
7. The catalytic cracking reaction method according to claim 6, wherein: The Y-type molecular sieve is at least one of PSRY molecular sieve, PSRY-S molecular sieve, PSRY molecular sieve containing rare earth, PSRY-S molecular sieve containing rare earth, USY molecular sieve, USY molecular sieve containing rare earth, REY molecular sieve, REHY molecular sieve and HY molecular sieve.
8. The catalytic cracking reaction method according to claim 1, wherein: The catalytic cracking reaction conditions include: a reaction temperature of 500-800°C.
9. The catalytic cracking reaction method according to claim 1, wherein: The hydrocarbon oil is selected from one or more of crude oil, naphtha, gasoline, atmospheric residue, vacuum residue, atmospheric wax oil, vacuum wax oil, straight-run wax oil, propane light / heavy deoiling, coker wax oil and coal liquefaction products.
10. A catalytic cracking aid, characterized in that: The catalytic cracking aid is composed of 20-80% of phosphorus-modified ZSM-5 molecular sieve, 1-70% of inorganic binder and 2-60% of clay on a dry basis, based on the dry basis weight of the catalytic cracking aid. The phosphorus-modified ZSM-5 molecular sieve has a binding energy of phosphorus element in phosphorus species on the surface of the molecular sieve of 134.6-134.7 eV after hydrothermal aging at 800° C. and 100% water vapor for 17 hours. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 10 to 25 ppm.
11. The catalytic cracking aid according to claim 10, wherein: The phosphorus-modified ZSM-5 molecular sieve is hydrothermally aged at 800°C and 100% steam for 17 hours. 27 In the Al MAS-NMR spectrum, the full width at half maximum of the resonance signal peak with a chemical shift of 39±3 ppm is 15 to 25 ppm.
12. The catalytic cracking aid according to claim 10, characterized in that: The phosphorus-modified ZSM-5 molecular sieve has a molar ratio of phosphorus to aluminum of 0.01 to 5, preferably 0.1 to 3.
13. The catalytic cracking aid according to claim 10, characterized in that: The phosphorus-modified ZSM-5 molecular sieve is obtained by impregnating the HZSM-5 molecular sieve with an aqueous solution of a phosphorus-containing compound having a phosphorus valence state of +1 at room temperature, such as 20-25°C, followed by drying and calcining; or, the phosphorus-modified ZSM-5 molecular sieve is obtained by mixing and grinding the HZSM-5 molecular sieve and a solid phosphorus-containing compound having a phosphorus valence state of +1, heating and melting the mixture, cooling the mixture to room temperature, such as 20-25°C, and then calcining the mixture.
14. The catalytic cracking aid according to claim 13, characterized in that: The impregnation has a water-to-screen weight ratio of 0.5-2 and is carried out at room temperature for 0.5-10 hours; the drying is carried out in an air atmosphere at 100-120°C for 2-24 hours; the calcination is carried out in an air atmosphere at 200-800°C for 0.5-12 hours.
15. The catalytic cracking aid according to claim 13, characterized in that: The heating and melting treatment has a temperature higher than the melting point of the solid phosphorus-containing compound and lower than the temperature at which the solid phosphorus-containing compound decomposes or dehydrates, and the treatment time is 2 to 72 hours.
16. The catalytic cracking aid according to claim 13, characterized in that: The phosphorus-containing compound with a phosphorus valence state of +1 is selected from one or more of hypophosphorous acid, ammonium hypophosphite, and hypophosphite; or, the aqueous solution of the phosphorus-containing compound with a phosphorus valence state of +1 is an aqueous solution of hypophosphorous acid adjusted to a pH value of 5-9 with ammonia water.
17. The catalytic cracking aid according to claim 13, characterized in that: The molar ratio of the HZSM-5 molecular sieve to the phosphorus-containing compound with a phosphorus valence state of +1 is (0.1-2.5):1, preferably (0.5-1.5):1, wherein the HZSM-5 molecular sieve is calculated as aluminum and the phosphorus-containing compound is calculated as phosphorus.
18. The catalytic cracking aid according to claim 10, wherein: The inorganic binder includes phosphorus-aluminum inorganic binder and / or other inorganic binders.
19. The catalytic cracking aid according to claim 18, wherein: The phosphorus-aluminum inorganic binder accounts for 5-40% by weight based on the dry basis of the additive.
20. The catalytic cracking aid according to claim 10, wherein: The inorganic binder also contains at least one other inorganic binder selected from pseudo-boehmite, aluminum sol, silica-alumina sol and water glass.
21. The catalytic cracking aid according to claim 10, wherein: The clay is selected from at least one of kaolin, sepiolite, attapulgite, rectorite, montmorillonite and diatomaceous earth.
